THE ROLE OF THE PRINCIPLE OF SCIENTIFIC RIGOR IN IMPROVING THE METHODOLOGY FOR DEVELOPING RESEARCH COMPETENCE AMONG MASTE’S STUDENTS IN CHEMISTRY (Web of Teachers: Inderscience Research, 2025)
In this article, the theoretical and methodological approaches to developing and enhancing the research competence of master’s students specializing in chemistry within the higher education system are reconsidered through the lens of the principle of scientific rigor. During the study, the essence of research competence, its structural components, and the mechanisms of its formation were thoroughly analyzed. Based on the findings obtained, effective methodological recommendations and improved pedagogical solutions aimed at further strengthening research competence among master’s students were developed.